# Rearranging Equations

Now that we have described the basic rules of negative and positive numbers and what to do when you add, subtract, multiply and divide them, we are ready to tackle some real mathematics problems! Earlier in this chapter, we wrote a general equation for calculating how much change (x) we can expect if we know how much an item costs (y) and how much we have given the cashier (z).

The equation is: $x + y = z$

So, if the price is $10 and you gave the cashier$15, then write $15 instead of z and$10 instead of y. $x + 10 = 15$

Now that we have written this equation down, how exactly do we go about finding what the change is? In mathematical terms, this is known as solving an equation for an unknown (x in this case). We want to re-arrange the terms in the equation, so that only x is on the left hand side of the = sign and everything else is on the right. The most important thing to remember is that an equation is like a set of weighing scales. In order to keep the scales balanced, whatever, is done to one side, must be done to the other.

Method: Rearranging Equations You can add, subtract, multiply or divide both sides of an equation by any number you want, as long as you always do it to both sides.

Example
 So for our example we could subtract y from both sides $\begin{array}{rcl} x + y & = & z\\ x + y - y & = & z - y\\ x & = & z - y\\ x & = & 15 - 10\\ & = & 5 \end{array}$ Now we can see that the change is the price subtracted from the amount paid to the cashier. In the example, the change should be \$5. In real life we can do this in our heads; the human brain is very smart and can do arithmetic without even knowing it.

When you subtract a number from both sides of an equation, it looks just like you moved a positive number from one side and it became a negative on the other, which is exactly what happened. Likewise if you move a multiplied number from one side to the other, it looks like it changed to a divide. This is because you really just divided both sides by that number, and a number divided by itself is just 1

$\begin{array}{rcl} a(5 + c) & = & 3a\\ a(5 + c) \div a & = & 3a \div a\\ \frac {a}{a} \times (5 + c) & = & 3 \times \frac{a}{a}\\ 1 \times (5 + c) & = & 3 \times 1\\ 5 + c & = & 3\,\!\\ c & = & 3 - 5\\ c & = & -2 \end{array}$

## Possible Errors

However you must be careful when doing this, as it is easy to make mistakes. The following is the WRONG thing to do

$\begin{array}{rcl} 5a + c & = & 3a\\ 5 + c & = & 3 \end{array}$

Can you see why it is wrong? It is wrong because we did not divide the c term by a as well. The correct thing to do is

$\begin{array}{rcl} 5a + c & = & 3a\\ 5 + c \div a & = & 3\\ c \div a & = & 3 - 5\\ c \div a & = & -2 \end{array}$

Activity
 Rearrange these equations: If $3(2r - 5) = 27$, then $2r - 5 =$ ... Find the value for $x$ if $0.5(x - 8) = 0.2x + 11$ Solve $9 - 2n = 3(n + 2)$ Change the formula $P = A + Akt$ to $A =$ Solve for $x: \frac {1}{ax} + \frac{1}{bx} = 1$

# Media required

 A video demonstrating rearranging of equations.

Content from this page was originally sourced from http://www.fhsst.org/ which is licenced under the GFDL 1.2:

"Permission is granted to copy, distribute and/or modify this document under the terms of the GNU Free Documentation License, Version 1.2 or any later version published by the Free Software Foundation; with no Invariant Sections, no Front-Cover Texts, and no Back-Cover Texts. A copy of the license is included in the section entitled “GNU Free Documentation License”.